2017
DOI: 10.1080/15376516.2016.1273429
|View full text |Cite
|
Sign up to set email alerts
|

The effects of endoplasmic reticulum stress inducer thapsigargin on the toxicity of ZnO or TiO2 nanoparticles to human endothelial cells

Abstract: It was recently shown that ZnO nanoparticles (NPs) could induce endoplasmic reticulum (ER) stress in human umbilical vein endothelial cells (HUVECs). If ER stress is associated the toxicity of ZnO NPs, the presence of ER stress inducer thapsigargin (TG) should alter the response of HUVECs to ZnO NP exposure. In this study, we addressed this issue by assessing cytotoxicity, oxidative stress and inflammatory responses in ZnO NP exposed HUVECs with or without the presence of TG. Moreover, TiO NPs were used to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 25 publications
4
31
0
Order By: Relevance
“…For example, Montiel-Davalos et al (2012) reported that TiO 2 , an insoluble NP, could inhibit HUVEC proliferation and promote apoptosis and necrosis. However, we and others did not observe cytotoxic effects in HUVECs after TiO 2 NP exposure (Suzuki et al, 2014;Gu et al, 2017). The exact reason for the inconsistent reports remains unclear, but it has been suggested the relevant factors associated with the toxicological responses of NPs should be considered (Azhdarzadeh et al, 2015).…”
Section: Toxic Effects Of Nps To Huvecs Cytotoxicitymentioning
confidence: 59%
See 3 more Smart Citations
“…For example, Montiel-Davalos et al (2012) reported that TiO 2 , an insoluble NP, could inhibit HUVEC proliferation and promote apoptosis and necrosis. However, we and others did not observe cytotoxic effects in HUVECs after TiO 2 NP exposure (Suzuki et al, 2014;Gu et al, 2017). The exact reason for the inconsistent reports remains unclear, but it has been suggested the relevant factors associated with the toxicological responses of NPs should be considered (Azhdarzadeh et al, 2015).…”
Section: Toxic Effects Of Nps To Huvecs Cytotoxicitymentioning
confidence: 59%
“…Similarly, Chen et al () showed that exposure to ZnO NPs induced the expression of a panel of ER stress markers before inducing apoptosis. However, in our recent study, stressing HUVECs with ER stress inducer did not significantly affect the toxicity of ZnO NPs (Gu et al, ). Rather, activation of macrophages with a ER stress inducer promoted the toxicity of ZnO NPs to macrophages, which could be further transferred to HUVECs in macrophage–endothelial co‐cultures (Chen et al, ).…”
Section: Mechanisms For the Adverse Effectsmentioning
confidence: 62%
See 2 more Smart Citations
“…Exposure to ZnO nanoparticles (NPs; definition similar to NMs) has been shown to activate ER stress‐apoptosis pathways both in vivo and in vitro, which could be the molecular mechanisms underlying the toxicity of ZnO NPs (Chen et al, ; Yang et al, ). Moreover, modulation of ER stress by chemicals could alter ZnO NP‐induced cytotoxicity and/or inflammatory responses, which further suggested a role of ER stress in determining the toxic effects of ZnO NPs (Chen et al, ; Gu et al, ). However, relatively few studies assessed the possible role of physicochemical properties in ZnO NP‐induced ER stress and toxicity.…”
Section: Introductionmentioning
confidence: 99%